Penerapan Media Komik Bergambar untuk Meningkatkan Nilai Tanggung Jawab Siswa pada Mata Pelajaran Bahasa Indonesia Kelas II SD - Fitriana Fitriana; Ibnu Muthi (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study aims to examine the application of illustrated comic media in Indonesian language learning as an effort to improve the responsibility values ​​of grade 2 elementary school students. The value of responsibility is an important part of character education that needs to be instilled early on, especially through an approach that is appropriate to the child's developmental stage. The methodology used in this study is a literature study, by reviewing a number of sources such as scientific journals, reference books, and previous research reports that are relevant to the use of comic media in the context of learning and strengthening character. The results of the study indicate that illustrated comic media can be an effective means of conveying moral messages because it combines visual and narrative aspects that are interesting for early childhood students. Comics allow the presentation of responsibility values ​​through characters and storylines that are easy to understand and serve as role models for students. In the context of Indonesian language learning, comics also support reading skills and understanding the contents of the story, while facilitating discussion of the values ​​contained therein. The conclusion of this study shows that the use of illustrated comic media in a planned and systematic manner can contribute positively to improving students' understanding and application of responsibility values ​​in everyday life. This media also supports the creation of fun, meaningful, and contextual learning for elementary school students.